Identification of outliers in a genomic scan for selection along environmental gradients in the bamboo locust, Ceracris kiangsu - Feng, Xiao-Jing (Sci Rep, 2015)
Identification of loci under divergent selection is a key step in understanding the evolutionary process because those loci are responsible for the genetic variations that affect fitness in different environments. Understanding how environmental forces give rise to adaptive genetic variation is a challenge in pest control. Here, we performed an amplified fragment length polymorphism (AFLP) genome scan in populations of the bamboo locust, Ceracris kiangsu, to search for candidate loci that are influenced by selection along an environmental gradient in southern China. In outlier locus detection, loci that demonstrate significantly higher or lower among-population genetic differentiation than expected under neutrality are identified as outliers. We used several outlier detection methods to study the features of C. kiangsu, including method DFDIST, BayeScan, and logistic regression. A total of 97 outlier loci were detected in the C. kiangsu genome with very high statistical supports. Moreover, the results suggested that divergent selection arising from environmental variation has been driven by differences in temperature, precipitation, humidity and sunshine. These findings illustrate that divergent selection and potential local adaptation are prevalent in locusts despite seemingly high levels of gene flow. Thus, we propose that native environments in each population may induce divergent natural selection.